DETERMINANTS OF DIVIDEND PAYOUT DECISIONS OF ORGINAL EQUIPMENT MANUFACTURERS FROM INDIAN AUTOMOBILE INDUSTRY - Kaur, Navleen (Copernican Journal of Finance & Accounting, 2021)
The purpose of this study is to identify and analyze the variables that significantly affect dividend payout decisions of Original Equipment Manufacturers (OEMs) from Indian automobile industry listed on the Bombay Stock Exchange (BSE). Analysis is based on balanced panel data with 180 observations of 12 companies over a period of 15 years i.e. from 2003-04 to 2017-18. Descriptive analysis, correlation analysis, and static panel data regression analysis including regression diagnostics have been used as statistical tools to achieve the purpose of the study. STATA software was used to analyze the data in the present study. The findings indicate that the significant determinants of dividend payout decisions of sample companies during the study period were profitability, size, book value per share, tangibility of assets, leverage and price earnings ratio. The findings of the study support various theories of dividend policy viz. Signalling, Pecking Order, and Transaction Cost. As per authors’ knowledge, this is the first study focusing on the determinants of dividend payout decisions of OEMs in India using the data from 2003-04 to 2017-18. The empirical findings of the present study will provide useful insight pertaining to dividend payout decisions to various stakeholders of different companies and will also be helpful to the future researchers.